Extract of Isatidis Radix Inhibits Lipid Accumulation in In Vitro and In Vivo by Regulating Oxidative Stress - Yo-Han Han; Ji-Ye Kee (MDPI AG, 2023)
Isatidis Radix (IR), the root of Isatis tinctoria L. belonging to Brassicaceae, has been traditionally used as a fever reducer. Although some pharmacological effects, such as anti-diabetes, anti-virus, and anti-inflammatory, have been reported, there is no study on the anti-obesity effect of IR. This study used 3T3-L1 cells, human mesenchymal adipose stem cells (hAMSCs), and a high-fat diet (HFD)-induced obese mouse model to confirm the anti-adipogenic effect of IR. Intracellular lipid accumulation in 3T3-L1 cells and hAMSCs was decreased by IR treatment.IR extract especially suppressed reactive oxygen species (ROS) production through a cluster of differentiation 36 (CD36)-AMP-activated protein kinase (AMPK) pathway. Consequently, the expressions of peroxisome proliferator-activated receptor gamma (PPARγ), CCAAT-enhancer-binding proteins alpha (C/EBPα), and fatty acid synthesis (FAS) were inhibited by IR extract. In addition, β-oxidation-related genes were also decreased by treatment of IR extract. IR inhibited weight gain through this cascade in the HFD-induced obese mouse model. IR significantly suppressed lipid accumulation in epididymal white adipose tissue (eWAT). Furthermore, the administration of IR extract decreased serum free fatty acid (FFA), total cholesterol (TC), and LDL cholesterol, suggesting that it could be a potential drug for obesity by inhibiting lipid accumulation.